Therapeutic drug monitoring of adalimumab in hidradenitis suppurativa: a prospective observational study - Chen, Stella X.; Wafae, Bruna Galvao de O.; Look-Why, Sydney; Otto, Tracey; Snyder, Corey; Sweet, William; Ashina, Nazrin; Gibson, Ruby; Salian, Prerna; Doroudian Tehrani, Maneli; Dervieux, Thierry; Kimball, Alexa B.; et al. (Frontiers in Immunology, 2026)
BackgroundAdalimumab (ADA) is an effective treatment for moderate to severe hidradenitis suppurativa (HS). However, nearly half of patients receiving the standard dose may lose response.ObjectiveTo establish therapeutic thresholds for HS-specific ADA levels, leading to more personalized treatment.MethodsWe conducted a single-center, prospective observational study of adults with HS treated with ADA (40 or 80mg/week, and 80mg/biweekly) at a specialized HS clinic (January 2023–May 2024). Serum samples were collected after ≥4 weeks of therapy to ensure steady state. Patients were stratified by physician-assessed response (low <50%, partial 50–75%, high >75% improvement). Associations of ADA concentration and clearance with response were tested using Spearman and Pearson correlations; discriminatory performance was evaluated with ROC analysis.ResultsAmong 46 enrolled patients, the majority was female (60.9%) and White (54.3%), with a median age of 38 years (IQR: 30–45). ADA serum concentrations positively correlated with clinical response (r = 0.43, p = 0.002). Low responders had significantly lower concentrations than partial (p = 0.029) and high responders (p = 0.007). Clearance was inversely correlated with ADA levels (r = –0.65, p < 0.001). Receiver operating characteristic analysis identified optimal thresholds of 10.7 μg/mL for ADA concentration and 0.5 L/day for clearance.ConclusionHigher ADA concentrations and lower drug clearance are associated with better clinical outcomes in HS. ROC analysis identified 10.7 μg/mL (ADA concentration) and 0.5 L/day (clearance) as optimal cut-off values to differentiate low from partial/high responders. These findings suggest that therapeutic drug monitoring may help optimize ADA therapy in HS.